DEKADENSI PARTISIPASI POLITIK DAN KEPERCAYAAN PUBLIK: PERSPEKTIF DAN STRATEGI MITIGASI PARTAI POLITIK - Keynagaya Ahmadine Surya; Muhammad Adel Nurfirmansyah; Uswatun Khasanah; Tia Fahira Septiana; Rivan Dwi Kurniawan; Sri Untari (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2025)
The political role in the governance of Indonesia focuses on the function of political parties as an important part of the political infrastructure. Based on Law No. 2 of 2011, political parties have the function of providing political education, creating unity, and channeling the aspirations of the people. However, there is a decline in public trust in political parties as reflected in surveys and a decrease in electoral participation. This research uses a qualitative method with interview and observation approaches to examine the perspectives and mitigation strategies of the political parties Gerindra and PKB in increasing public trust. The results show that political apathy, especially among millennials and Gen Z, arises due to a lack of political education, as well as the influences of globalization and westernization. This apathy contributes to a decline in political participation and trust in political parties, which poses a significant challenge to democracy in Indonesia. The mitigation efforts undertaken by political parties need to be strengthened in order to improve their image and increase public participation in a more meaningful and responsible political life. Active participation and public trust are the pillars of a strong democracy; the success of political parties in fulfilling their functions will determine the future of democracy in Indonesia. Peran politik dalam ketatanegaraan Indonesia dengan fokus pada fungsi partai politik sebagai bagian penting infrastruktur politik. Berdasarkan Undang-Undang Nomor 2 Tahun 2011, partai politik memiliki fungsi memberikan pendidikan politik, menciptakan persatuan, dan menyalurkan aspirasi rakyat. Namun, terdapat penurunan kepercayaan publik terhadap partai politik yang tercermin dari survei dan turunnya partisipasi pemilu. Penelitian ini menggunakan metode kualitatif dengan pendekatan wawancara dan observasi untuk mengkaji perspektif dan strategi mitigasi partai politik dari Partai Gerindra dan PKB dalam meningkatkan kepercayaan publik. Hasil penelitian menunjukkan bahwa apatisme politik, terutama di kalangan milenial dan Gen Z, timbul karena kurangnya pendidikan politik, serta pengaruh globalisasi dan westernisasi. Apatisme tersebut berkontribusi pada menurunnya partisipasi politik dan kepercayaan terhadap partai politik, yang menjadi tantangan signifikan bagi demokrasi di Indonesia. Upaya mitigasi yang dilakukan partai politik perlu diperkuat agar dapat memperbaiki citra dan meningkatkan partisipasi masyarakat dalam kehidupan berpolitik yang lebih bermakna dan bertanggung jawab. Partisipasi aktif dan kepercayaan publik merupakan pilar demokrasi yang kokoh, keberhasilan partai politik dalam menjalankan fungsinya akan menentukan masa depan demokrasi Indonesia.